Legal Construction and Obligations of Tourism Business Operators Towards the Principles of Sustainable Tourism in the Perspective of Tourism Law - I Made Adi Ananda Permana; Dewa Krisna Prasada; Anak Agung Ayu Ngurah Sri Rahayu Gorda; Dewa Ayu Putri Sukadana (LOCUS MEDIA PUBLISHING, 2025)
This study discusses the legal framework and the obligations of tourism operators in implementing the principles of sustainable tourism in Indonesia. The main focus of this research is to analyze the implementation of sustainability principles within Law No. 10 of 2009 on Tourism and related international regulations such as ISO 21401 and the International Tourism Ethics Code. The methodology used is normative legal research with legislative and conceptual approaches, aiming to critique ambiguities in existing regulations and propose solutions regarding the obligations of tourism operators. The findings show that there is a lack of clarity in the legal provisions regulating sustainability, which may negatively impact social and environmental aspects. Therefore, this study suggests the need for revisions to clarify the obligations of tourism operators to conduct environmental and social impact assessments. In conclusion, the study advocates for a stronger integration of national regulations with international standards to ensure the development of tourism that is sustainable, equitable, and environmentally friendly.